Isoflurane's Effect on Protein Conformation as a Proposed Mechanism for Preconditioning - Michelle R. Baker; Sean K. Benton; Christopher S. Theisen; Chad A. McClintick; Eugene E. Fibuch; Norbert W. Seidler (Biochemistry Research International)
Persistent alteration of protein conformation due to interaction with isoflurane may be a novel molecular aspect of preconditioning. We preincubated human serum albumin with isoflurane, dialyzed to release agent, and assessed protein conformation. Susceptibility to chemical modification by methylglyoxal and nitrophenylacetate was also examined. Isoflurane had a persistent effect on protein conformation. An increase in the susceptibility of surface residues to chemical modification attended this change in conformation. Modification of isoflurane-treated HSA included intra- and intersubunit cross-linking that may be a consequence of anesthetic-induced changes in multimeric subpopulations. This irreversible effect of isoflurane may represent a mechanism for preconditioning.